Diseño e implementación de un sistema de virtualización con KVM, utilizando la infraestructura del data center experimental para los laboratorios de cómputo FICA de la UDLA - Cortez Plaza, Bryan Eduardo (2018)
This titling project will contemplate the design and implementation of a virtualization system with KVM using the experimental Data Center, which is focused on the FICA laboratories of the University of the Americas, in order to obtain a saving of technological resources. In the first place, the analysis of characteristics, operation, requirements about the KVM will be carried out, plus the description of the components it has. The information on the virtualization technologies that the laboratories have will also be compiled and analyzed. The corresponding information will be obtained of how the virtualization with which the Data Center is composed. Finally, with the information obtained, the virtualization technology will be implemented, where tests and analysis of the operation of the system will be carried out.